The Role of Cardiopulmonary Exercise Test in IPF Prognosis. (31st October 2013) - Triantafillidou, Christina; Manali, Effrosyni; Lyberopoulos, Panagiotis; Kolilekas, Likourgos; Kagouridis, Konstantinos; Gyftopoulos, Sotirios; Vougas, Konstantinos; Kotanidou, Anastasia; Alchanatis, Manos; Karakatsani, Anna; Papiris, Spyros A.
Abstract : Background . In IPF, defects in lung mechanics and gas exchange manifest with exercise limitation due to dyspnea, the most prominent and disabling symptom. Aim . To evaluate the role of exercise testing through the 6MWT (6-minute walk test) and CPET (cardiopulmonary exercise testing) in the survival of patients with IPF. Methods . This is a prospective, observational study evaluating in 25 patients the relationship between exercise variables through both the 6MWT and CPET and survival. Results . By the end of the observational period 17 patients were alive (33% mortality). Observation ranged from 9 to 64 months. VE/VCO2 slope (slope of relation between minute ventilation and CO2 production), VO2 peak/kg (peak oxygen consumption/kg), VE/VCO2 ratio at anaerobic threshold, 6MWT distance, desaturation, and DLCO% were significant predictors of survival while VE/VCO2 slope and VO2 peak/kg had the strongest correlation with outcome. The optimal model for mortality risk estimation was VO2 peak/kg + DLCO% combined. Furthermore, VE/VCO2 slope and VO2 peak/kg were correlated with distance and desaturation during the 6MWT. Conclusion . The integration of oxygen consumption and diffusing capacity proved to be a reliable predictor of survival because both variables reflect major underlying physiologic determinants of exercise limitation.